The conflict between NETs and LETs in a Chinese medium of instruction in secondary school in Hong Kong - Chan, Hoi Yuen (Journal of Interdisciplinary Studies in Education, 2012)
The Hong Kong government has employed native English speaking teachers (NETs) to teach English in secondary schools since 1987. This scheme has been scrutinized by many educators, students, and parents. One concern has involved the effectiveness of NETs in teaching English when compared to local English teachers (LETs). This article looks at the history of NET scheme, the tensions between NETs and LETs from an insider’s view, and the effectiveness of instruction between NETs and LETs. Recommendations are provided for prospective NETs and local educators in Hong Kong.